All in Pasaje Esperanza: how Chilean telenovela Verdades Ocultas became a streaming soap opera - Bruna, Alejandro (2022)
On July 24, 2017, Chileans were hooked with the long-suffering story of the Verdugo sisters in Verdades Ocultas, a Chilean telenovela anchored in structural concepts of classic melodrama (Fuenzalida, Corro & Mujica, 2009; Cabrujas, 2002). Its success prompted an unexpected lengthening, becoming the longest telenovela in Chilean history to date. Yet narrative shifts led to ample changes regarding dramatic structure and the seriality inherent to its genre (Buonnano, 2005), fluctuating from a telenovela (Mazziotti, 2009; Martín Barbero, 2002) to a soap opera (Allen, 1995; Harrington, 2016), giving way to a product perfect for streaming.